Developmental Dyslexia and Phonological Processing in European Portuguese Orthography - Moura, Octávio (2015)
This study analysed the performance of phonological processing, the diagnostic accuracy and the influence on reading in children who were native speakers of an orthography of intermediate depth. Portuguese children with developmental dyslexia (DD; N=24; aged 10-12 years), chronological age (CA)-matched controls (N=24; aged 10-12 years) and reading level (RL)-matched controls (N=24; aged 7-9 years) were tested on measures of phonological processing (phonological awareness, naming speed and verbal short-term memory) and reading. The results indicated that the children with DD performed significantly poorer in all measures compared with the CA and RL. Phonological awareness and naming speed showed a high accuracy (receiver operating characteristics curve analysis) for discriminating the children with DD from the CA and RL, whereas the presence of abnormally low scores in phonological awareness and naming speed was more frequent in the DD group than in the controls and the normative population. Hierarchical linear regression analyses revealed that phonological awareness was the most important predictor of all reading accuracy measures, whereas naming speed was particularly related to text reading fluency.